Quantitative Analysis of Skin Erythema Due to Laser Hair Removal: A Diffusion Optical Spectroscopy Analysis - Babadi, Mozhdeh; Mohajerani, Ezeddin; Ataie Fashtami, Leila; Zand, Nasrin; Shirkavand, Afshan (Journal of Lasers in Medical Sciences, 2019)
Introduction: Laser hair removal needs an accurate understanding of tissue structure and chromophores content in order to optimize the selection of laser irradiation parameters. None of the optimized laser therapy might lead to side effects in skin tissue such as severe erythema, burn, scar etc. Therefore, guidance by a noninvasive real-time diagnostic method like optical spectroscopy technique is beneficial. The purpose of this survey is to analysis the skin hemoglobin spectrum quantitatively before and after hair removal laser irradiation to minimize the side effects of the procedure. Methods: To carry out a spectroscopy study, a halogen-tungsten light source was used in the wavelength region of 400-700 nm on an ocean optic device. The measurements were made on the facial area under identical conditions. Total 19 volunteers for laser hair removal by gentle laser Candela, ranging 14- 49 years old, were included in the study. A total of 18 spectra were taken from each person, 9 spectra before hair removal as a reference and 9 subsequent spectra. Colorimetry was done for all acquired before and after spectrums using Origin software (version 8.6). Then, the erythema index derived for each spectrum. Statistical analysis of correlation and normalization in colorimetry data were done using data analysis by SPSS (version 16). Results: Spectra analysis, before and after optical reflectance spectrums in laser hair removal procedure, revealed the subpeak derivation, and concentration on special visible wavelength 510-610 nm. We studied the changes of skin chromophores absorption. The derived erythema index [E] and colorimetry parameters a*, b*, l* were compared and correlated statistically. There was a statistically considerable direct linear correlation between a* and E while inverse linear correlation was observed for l* and E and no correlation for b* and E. Conclusion: Diffuse reflectance spectroscopy showed its potency as an accurate, noninvasive real-time as complementary method for laser treatment to detect erythema as a complication of the method, in order to optimize the parameters based on the tissue characteristics in various candidates.